2023
DOI: 10.3390/s23063313
|View full text |Cite
|
Sign up to set email alerts
|

Programmable Nanostructures Based on Framework-DNA for Applications in Biosensing

Abstract: DNA has been actively utilized as bricks to construct exquisite nanostructures due to their unparalleled programmability. Particularly, nanostructures based on framework DNA (F-DNA) with controllable size, tailorable functionality, and precise addressability hold excellent promise for molecular biology studies and versatile tools for biosensor applications. In this review, we provide an overview of the current development of F-DNA-enabled biosensors. Firstly, we summarize the design and working principle of F-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 157 publications
(194 reference statements)
0
4
0
Order By: Relevance
“…As aforementioned, the unique properties of DNA/nucleic acids and the nanomaterials’ intrinsic features have led to a keen interest to employ nucleic acids in the manufacture of reliable biosensors. DNA has played a key role in organisms and emerged in time with superior properties . DNA has emerged as a durable sensor component that led to the design of robust DNA sensors; similarly, DNA has been studied for its multiple advantageous roles such as mechanical stability, programmable stability, well-known thermal stability, and predictable reactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As aforementioned, the unique properties of DNA/nucleic acids and the nanomaterials’ intrinsic features have led to a keen interest to employ nucleic acids in the manufacture of reliable biosensors. DNA has played a key role in organisms and emerged in time with superior properties . DNA has emerged as a durable sensor component that led to the design of robust DNA sensors; similarly, DNA has been studied for its multiple advantageous roles such as mechanical stability, programmable stability, well-known thermal stability, and predictable reactions.…”
Section: Introductionmentioning
confidence: 99%
“…17 emerged in time with superior properties. 18 DNA has emerged as a durable sensor component that led to the design of robust DNA sensors; similarly, DNA has been studied for its multiple advantageous roles such as mechanical stability, programmable stability, well-known thermal stability, and predictable reactions. In earlier decades, DNA has been used to engineer scaffolds with mechanical stabilities in extreme conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Biosensors are devices composed of a biorecognition part and of a transduction part. Natural biomolecules such as enzymes [ 1 ], antibodies [ 2 ], DNA strains [ 3 ], bacteria and yeast [ 4 , 5 ], cells and even plant/animal tissues can constitute the recognition part. Synthesized polymers such as MIP (molecularly imprinted polymers) [ 1 ], aptamers and peptides can also be used as recognition part.…”
mentioning
confidence: 99%
“…It was demonstrated that streptavidin is preferable to neutravidin for constructing lipid bilayers based sensing platforms [ 7 ]. Nanostructures based on framework DNA hold excellent promise for molecular biology studies and versatile tools for biosensor applications as reviewed in [ 3 ]. Dynamic mode decomposition of fluorescence loss was also used for monitoring protein diffusion, protein assemblies and protein aggregates in living cells [ 8 ].…”
mentioning
confidence: 99%